(untitled) (Colombia Medica, 1988)
We present the clinical experience derived from the retrospective study of 25 Takayasu arteritis cases seen at Hospital Universitario del Valle between 1970-1986. The disease predominated in females (21/4), with an age of onset usually less than 30 years (76%). The period is delayed, with an average of 40.9 months. In only six patients was the initial diagnosis that of Takayasu’s disease. In less than half of the cases, an acute inflammatory phase was observed. The predominant clinical features were headache, 92%; reduction of the amplitude of peripheral arterial pulses, 76%; vascular and cardiac brutish, 76%; and raised blood pressure, 56%. All patients had multiple sites of arterial involvement documented by angiography. The most frequent variety of Takayasu’s disease was Type III (40%), and the most common finding of laboratory alteration was the elevation of erythrocyte sedimentation rate (100%). Treatment with corticosteroids improved dramatically the systemic symptoms but had a poor effect on the return of pulses. The surgical procedure usually had a good response.